Family climate influences. Learning strategies and emotional intelligence in the academic performance - Sotil Brioso, Amparo (2002)
The present work has as purpose to make an empiric study of the contribution of the combined effects of the family climate, the learning strategies and the emotional intelligence on the academic yield investigation carried out in a sample of 250 students of the Ability of Psychology of the National University bigger than San Marcos. Finding as a result that, as for the Family Climate the hall and balanced range families prevail, while regarding the emotional intelligence, an emotional capacity is observed below the average in the component personal intra. For I finish. it is of standing out that although a correlation exists statistically significant among the family types, the emotional intelligence and the learning strategies however, between these variables and the academic yield evaluated through the pondered average of the qualifications obtained by the students during its permanency in the university, a significant statistical correlation doesn't exist.